Effectiveness of Project Based Learning Model on Collaborative Ability and Critical Thinking of Senior High School Students - Slamet Riyadi, Ahmad; Alimah, Siti; Saptono, Sigit (Journal of Innovative Science Education, 2020)
In this 21st century educational, students are required to be able to have collaborative competence and critical thinking. So that, the school should be able to prepare students with such competences. This is an increasingly competitive challenge in the world of education. The research aims to analyse the effectiveness of PjBL learning models on the collaborative ability and critical thinking of senior high school students on subject of Structure, Way of Life and Role of Bacteria in Life. The method in this research was experimental research with Pre-Experimental design. The research was conducted at SMA Negeri 13 Semarang and MA Nurussalam Semarang with a total of 45 students. We used observation sheets and tests as the instrument. The observation sheet was used to measure collaborative ability while test was used to measure critical thinking skills. The data analysis techniques used standard of criteria and N-gain. Standard of criteria to measure collaborative ability while N-gain to measure increased critical thinking ability. The results of the research obtained (1) The average percentage of the collaborative ability score of class X IPA 2 SMA Negeri 13 Semarang is 71.6% while the class X IPA MA Nurussalam is 71.0%; (2) in the first test, the average percentage of critical thinking ability of class X IPA 2 SMA Negeri 13 Semarang is 62.9% while the class X IPA MA Nurussalam is 78.3%. In the second test, the average percentage of the critical thinking ability score of class X IPA 2 SMA Negeri 13 Semarang is 75.1% while the class X IPA MA Nurussalam is 80.0%. Both classes experienced an increase in the average percentage score of critical thinking abilities. The class X IPA 2 SMA Negeri 13 Semarang has increased by 12.2% while X IPA MA Nurussalam has an increase of 1.7%. Based on the research results it can be concluded that the implementation of PjBL learning model is effective on improving collaborative ability and critical thinking of students in SMA Negeri 13 Semarang and MA Nurussalam Semarang